Heavy Metals Bioaccumulation of Several Bradyrhizobium japonicum Strains - ADE NOOR SYAMSUDIN; TEDJA -IMAS; SUMINAR SETIATI ACHMADI (HAYATI Journal of Biosciences, 2005)
Heavy metal utilization in industry and agriculture have caused an environmental problem to existing life. Bioaccumulation is made up by a concentration of certain chemical compounds in living tissues. The objective of this research was to reveal the ability of lipopolysaccharides (LPSs) of heavy metal Bradyrhizobium japonicum tolerant strains in accumulating heavy metals. The strains used were BDG 10, KDR 10, and KDR 15. The ability of each strains on heavy metal accumulation of Cu, Pb, Zn, Ni, and Cd were quantitatively determined using atomic absorption spectrophotometry. The result showed that each strains has its own capacity to accumulate heavy metals. Accumulation of Cu (0.100), Pb (0.320), and Cd (0.048) ppm/mg dry weight by KDR 10 seem higher than BDG 10 and KDR 15. The highest accumulation of Zn and Ni was shown by KDR 15 in which the value were 0.360 and 0.165 ppm/mg dry weight, respectively and the least accumulation of all heavy metal studied was shown by BDG 10.